Efeitos dos esteroides anabólicos androgênicos sobre funções cognitivas de ratos - Silva, Fernando Roberto Ferreira (2014)
The use and the demand for substances that enhance masculinity, strength and sexual power are not novel. Over the years, this search has assisted the research directions in this area, leading to the discovery of the primary male sex hormone testosterone in 1935. Since then, numerous testosterone analogue compounds were synthesized, which are generically called Anabolic Androgenic Steroids (AAS). The AAS were produced for therapeutic purposes, but an increase in the use of these compounds for other purposes occurred over time. Initially they were used mainly to improve performance in athletes. However, recent studies have shown that the use of AAS by non-athletes with aesthetical purposes have been increasing as well. The abuse of AAS with non-clinical purposes can promote a number of physiological alterations, such as heart, liver, respiratory and psychological problems such as changes in mood, levels of anxiety and aggression. Exposure to supraphysiological doses of AAS is associated with behavioral changes, however, little is known about the effects of AAS on cognitive functions. In this work, we aimed to mimic the AAS abuse in humans with intramuscular administration of a supraphysiological dose of testosterone propionate (TP) in rats. We investigated the effects of this treatment on different aspects of cognitive function, specifically learning, memory and anxiety. Adult male Wistar rats were tested in the spontaneous alternation, novel object recognition and plus-maze discriminative avoidance tasks. The control group received intramuscular injections of vegetable oil (vehicle), and the TP group received injections of TP (10 mg/kg, i.m.). The injections were administered for 40 days, with intervals of 48 hours (chronic treatment) or in a single injection (acute treatment). In addition to the behavioral assessments, we performed biochemical analyzes as indicators of the endocrine effects of the treatment. Our results show that chronic treatment with a supraphysiological dose of TP caused memory impairments in the novel object recognition and the discriminative avoidance tasks. The spatial working memory (evaluated by spontaneous alternation task) was not affected. Also, we did not observe changes in anxiety levels. Regarding the biochemical parameters, chronic treatment increased serum levels of glutamicpyruvic transaminase, an indicator of hepatic and pancreatic lesions (as those observed after chronic use of these substances in humans). On the other hand, acute treatment with PT did not promote significant changes in any of these parameters when compared to the control group. In summary, we conclude that chronic treatment with a supraphysiological dose of testosterone propionate produces memory deficits in novel object recognition and retrieval of the discriminative avoidance task in adult male rats